Queuosine‐modified tRNAs confer nutritional control of protein translation. (9th August 2018) - Tuorto, Francesca; Legrand, Carine; Cirzi, Cansu; Federico, Giuseppina; Liebers, Reinhard; Müller, Martin; Ehrenhofer‐Murray, Ann E; Dittmar, Gunnar; Gröne, Hermann‐Josef; Lyko, Frank
Abstract: Global protein translation as well as translation at the codon level can be regulated by tRNA modifications. In eukaryotes, levels of tRNA queuosinylation reflect the bioavailability of the precursor queuine, which is salvaged from the diet and gut microbiota. We show here that nutritionally determined Q‐tRNA levels promote Dnmt2‐mediated methylation of tRNA Asp and control translational speed of Q‐decoded codons as well as at near‐cognate codons. Deregulation of translation upon queuine depletion results in unfolded proteins that trigger endoplasmic reticulum stress and activation of the unfolded protein response, both in cultured human cell lines and in germ‐free mice fed with a queuosine‐deficient diet. Taken together, our findings comprehensively resolve the role of this anticodon tRNA modification in the context of native protein translation and describe a novel mechanism that links nutritionally determined modification levels to effective polypeptide synthesis and cellular homeostasis. Synopsis: The modification of certain tRNAs depends on diet‐supplied precursor queuine. The queuosinylation of tRNAs affects methylation on neighbouring nucleotides and controls translational speed, illustrating how a nutritionally determined tRNA modification can affect polypeptide synthesis and cellular homeostasis in vivo . Dnmt2‐dependent tRNA methylation is dynamically modulated by nutritionally determined queuosine‐tRNA levels. Queuosine‐tRNA levels control the translation speed of queuosinylated‐tRNA decoded codons. Altered translation in the absence of queuosine results in misfolded aggregates, which in turn trigger endoplasmic reticulum stress and the unfolded protein response. Abstract : Queuosine modification of tRNAs requires the diet‐supplied precursor queuine. Q‐bearing tRNAs control translational speed, illustrating how a nutritionally determined tRNA modification can affect polypeptide synthesis and cellular homeostasis in vivo .